Surabhi Mittal on Mobile phone-enabled agro-advisory services - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Mobile phone-enabled agro-advisory services: a means to empower women farmers Presentation by Surabhi Mittal from CIMMYT at the seminar on Closing the gender gap in farming under climate change held 19 March 2015 in Paris. Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action